Factors in team effectiveness: Cognitive and demographic similarities of software development team members. - Kang, Hye-Ryun; Yang, Hee-Dong; Rowley, Chris (Human Relations, 2006)
The benefits of teams and teamwork are popular and propounded in management discourse. The use of this lexicon is based on beliefs in the resultant mutual gains for both organizations and individuals. Yet, are all teams, irrespective of the characteristics of membership composition, the same in terms of such beneficial outcomes? This study investigates the importance of team member characteristics, particularly cognitive and demographic, on team effectiveness and which characteristics matter more in team activities, especially where labour turnover is high, such as in software development. The Shared Mental Model is outlined and used as the representative construct for cognitive similarities; while age, tenure and gender are the demographic aspects used. From the relevant literature we develop a hypothesis and subject it to a range of tests based on empirical fieldwork using software development teams in South Korea. Our analysis shows that team effectiveness is more influenced by cognitive than demographic similarities. The implications and limitations of this work are detailed, with its wider relevance to international management, business and practice and other countries, noted. Reprinted by permission of the publisher.